2014
DOI: 10.1299/jamdsm.2014jamdsm0040
|View full text |Cite
|
Sign up to set email alerts
|

A five-axis CNC machining method of orthogonal variable transmission ratio face gear

Abstract: In order to verify the validity of the design for the orthogonal variable transmission ratio face gear pair, a five-axis CNC machine tool was used to machine this gear. The cutter tooth profile coordinate system, orthogonal variable ratio face gear machining coordinates, the model for the round-corner at tooth tip, the contact line model and CNC machining models were established by using space gear meshing theory and the machining principle of five-axis CNC machine tools. The method of machining this gear alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…During the transmission process of EHCF gear, on the assumption that a helical cutter is internal meshing with the HNC gear, at this time, the helical cutter can be seen to externally mesh with the EHCF gear, so the trajectory of meshing process of EHCF gear can be represented as shown in Fig.5(a) ( Lin et al, 2014a). …”
Section: The Trajectory Of Helical Cuttermentioning
confidence: 99%
See 1 more Smart Citation
“…During the transmission process of EHCF gear, on the assumption that a helical cutter is internal meshing with the HNC gear, at this time, the helical cutter can be seen to externally mesh with the EHCF gear, so the trajectory of meshing process of EHCF gear can be represented as shown in Fig.5(a) ( Lin et al, 2014a). …”
Section: The Trajectory Of Helical Cuttermentioning
confidence: 99%
“…Therefore, based on the researches of face gear, Lin Chao et al have proposed a new type of gear pair named curve-face gear pair, it can transfer the movement of variable transmission ratio between intersected axes, and they have studied application and basic theory of the curve-face gear pair such as design method, processing method, measurement method, contact analysis et al (Lin et al, 2013(Lin et al, , 2014a(Lin et al, , 2015. Besides, Liu Dawei et al also put forward an irregular face gear, which can also transfer the movement of variable transmission ratio, and they focused on the geometrical model, tooth analysis and the basic meshing theory (Liu et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The torque applied on the ORC gear is 200Nm  . And the rotational speed is 20 / min r .The test gears were produced by DMU 60monoBLOCK five-axis CNC machine (Lin, et al, 2014) using ball end cutter, as shown in Fig. 10.…”
Section: Bending Stress Testmentioning
confidence: 99%
“…Studies on modification of tooth surface are also conducted on CNC machine tool, 21 as it is a preferred method to improve meshing characteristics of spiral bevel gears. Shih 22 proposed a novel ease-off flank modification methodology for spiral bevel and hypoid gears made by a modern Cartesian-type hypoid gear generator.…”
Section: Introductionmentioning
confidence: 99%